ANALISIS TINGKAT PENGEMBALIAN INVESTASI PT. CIPUTRA DEVELOPMENT TBK SEBELUM DAN SESUDAH PENGUMUMAN PANDEMI COVID-19 - Nur Haliza, Eka Yudhyani, dan Camelia Verahastuti (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
This study aims to determine the rate of return on investment at PT. CiputraDevelopment Tbk before and after the announcement of the covid-19 pandemic bycomparing the Return On Investment Ratio with The Industry Average Ratio. Theanalytical tool used in this study is the profitability ratio, namely the Return OnInvestment (ROI) Ratio and using The Industry Average Ratio. Data collectiontechniques are carried out by means of literature research, by collecting secondarydata in the form of financial reports of PT. Ciputra Development Tbk andcompanies in the property industry sector which are used as the calculation of theindustry average ratio. The analytical tool used in this study is the profitabilityratio, namely the Return On Investment (ROI) Ratio and using The IndustryAverage Ratio. The results of this study is the rate of return on investment at PT.Ciputra Development Tbk in 2019 the first quarter of the company was in goodcondition, in 2019 the second quarter of the company was in poor condition, whilein 2019 the third quarter to 2020 the third quarter of the company was back in goodcondition. The conclusion of this study is that the condition of the company is notgood in 2019 the second quarter, because the return on investment ratio is belowthe industry average ratio.